Language acquisition and the functional category system - Jordens, Peter (Studies on language acquisition, 2012)
Finiteness, as a concept of information structure, determines the perspective from which the present investigation has been carried out. The linguistic status of finiteness in learner languages changes as a function of language development. This accounts for the fact that at consecutive stages of acquisition finiteness is expressed differently. Finiteness, as it plays a role at different stages of development, serves thus as the anchoring point from which the dynamics of the process of language development both in L1 and L2 learners can be explained. The present study shows that in this proces.